A five domains assessment of sow welfare in a novel free farrowing system - Plush, Kate; Lines, David; Staveley, Lauren; D’Souza, Darryl; van Barneveld, Robert (Frontiers in Veterinary Science, 2024)
The Maternity Ring was developed as a free farrowing alternative that preserved space while providing the sow with unrestricted movement. The aim of this experiment was to apply the Five Domains model to assess sow welfare in the Maternity Ring in comparison to the farrowing crate. Eighty-eight sows were housed in a farrowing crate (FC) and 83 in a Maternity Ring (MR) and measures collected focused on nutrition, environment, health, behaviour and mental state outcomes. MR sows consumed less feed than FC sows (total feed intake; 93.8 ± 3.06 kg vs 111.2 ± 3.13 kg, p < 0.001), but had reduced P2 backfat loss during lactation (0.0 ± 0.11 vs 1.2 ± 0.11, p < 0.001). Fewer frustrated and pain related behaviours during farrowing were observed in MR sows (bar biting; FC 3.3 ± 2.12 vs MR 0.5 ± 0.29 events, p = 0.038, and back leg forward; FC 227 ± 50.7 vs MR 127 ± 26.4 events, p = 0.019), and a decreased proportion of MR sows had facial injuries after farrowing (10% CI [5, 20] vs 67% CI [47, 95], p < 0.001). More FC sows had udder damage at weaning (70% CI [48, 97] vs 10% CI [6, 24], p < 0.001) and their piglets were medicated more frequently when compared to those in MR (51% CI [40,61] vs 30% [21,41], p = 0.008). MR sows tended to have a higher reaction score to piglet processing (MR 2.0 ± 0.38 versus FC 1.2 ± 0.27, p = 0.094), and had more contact with piglets once the procedure was complete than FC sows (13.5 ± 2.55 vs 6.9 ± 1.26 events, respectively, p = 0.016). Whilst there was no difference in anticipation to a feeding event (p > 0.05), MR sows displayed a reduced startle response to an aversive noise stimulus at day 18 (FC 2.8 ± 0.35, MR 0.7 ± 0.16, p < 0.001). Using the Five Domains framework, sows housed in the MR during farrowing and lactation have improved welfare than those in FC and can be thought of as being in a positive affective state.